The Role of Religiosity in Enhancing Academic Persistence among Adolescents in Orphanages - Putri, Alifa Auliya; Thalib, Tarmizi; Gismin, Sitti Syawaliyah (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Adolescents require support from their parents to help them face the challenges that arise during their development. However, in reality, not all adolescents receive parental guidance, and some end up living in orphanages. Adolescents in orphanages tend to experience pressure and problems more easily, especially in the academic field. Initial data shows that orphanage adolescents are more prone to giving up when faced with academic failure, and some have not yet determined their goals or aspirations after completing their education, which relates to academic persistence. Adolescents with a high level of religiosity tend to have better guidance and resilience. This study investigates how religiosity influences academic persistence in orphanage adolescents, highlighting its significant contribution to fostering resilience and goal-setting. The sample in this study consisted of 361 respondents, all of whom were adolescents living in orphanages in Makassar, selected using purposive sampling. The measurement tools in this study used the Centrality of Religiosity Scale (CSR-15) with a Cronbach's Alpha coefficient of 0.713 and the Academic Persistence Scale with a Cronbach's Alpha coefficient of 0.672. The results show that religiosity influences academic persistence among adolescents in orphanages in Makassar, with a significance value of 0.000 (sig 0.000; sig < 0.05) and an R-square of 0.277 or a contribution effect of 27.7% contribution of religiosity to academic persistence and the broader implications. Based on the study's findings, orphanages should increase the focus on religious education to foster adolescents' motivation to continue and complete their education to the fullest.